Ataxia and Early Lead Exposure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effect of chronic exposure to lead on postural balance was studied in 162 six-year-old children examined in the Department of Environmental Health, and Children's Hospital Medical Center, University of Cincinnati Medical School, Cincinnati, OH.